Life Of Happiness In Thommayanti’s Buddhism Novels - Chakchai, Chetha; Sriyaphai, Worawat; Rukmanee, Somkiet (Chophayom Journal, 2016)
This article aims to analyze concept of happiness life in Thommayanti’s Buddhism novels. Five Buddhism novels were used for analysis: Cita, Jamee, Jharn, Rajavadee, and Vaisanavee. Buddhist concepts used for analysis wereas follows : Buddhist Dictionary, glossary edition, written byBrahma Kunaphorn(Por. Or. Payutto) (2013) ; Buddhadharmawritten byBrahma Kunaphorn(Por. Or. Payutto) (2012); Buddhist dharma and Society written by Mr. Pravet Wasee (1983) ; Buddhist dharma and intention of democracywritten by Buddhathasapicku (1993); Life and Buddist dharma in Technology society written by Buddham association (1989); Comparison of Religious written by Sujitra Onkhom (2002); Life and Buddhism written by Aphiwat Phosarn (2008). Basic, intermediate, and advanced were 3 levels of Buddha Dharma that were studied. The result shows that 5 Buddhism novels reflected the three truth of the dharma. The first truth is basic truth of dharma, Thithadhamikhatta: sources of happiness in the present life. The second truth is intimidate level of the dharma truth, Simprayikhatta: sources of happiness in the future life. The latter is advanced level of dharma truth, Parramatta: the Absolute Truth. Those are the truths that every man have to experience. Thommayanti tactically presented the story by raising a character with issues. Each character sought solutions to resolve the issues interestingly. If characters could exhale, eternal happiness would come. Three truths of the dharma which were the truth of being born, old, suffered, and died; the truth that everyone had to experience suffering; and the truth of the three Signata concept were put throughout the stories.Thommayantipropagated the truths of the dharma in each story through characters. Anyone whocautiously kept and considered Buddha’s dharma in their living would have happier life. Since knowing causes of suffering, you would see solution to resolve. Your sorrow would be relieved and happiness would come. Anyone who cautiously kept and considered the Three Signata in their living would relieve their sorrow. An eternity of happiness would come.